How Supraphysiological Oxygen Levels in Standard Cell Culture Affect Oxygen-Consuming Reactions. (30th September 2018) - Stuart, Jeffrey A.; Fonseca, Joao; Moradi, Fereshteh; Cunningham, Cassandra; Seliman, Bishoy; Worsfold, Cydney R.; Dolan, Sarah; Abando, John; Maddalena, Lucas A.
Abstract : Most mammalian tissue cells experience oxygen partial pressures in vivo equivalent to 1–6% O2 (i.e., physioxia). In standard cell culture, however, headspace O2 levels are usually not actively regulated and under these conditions are ~18%. This drives hyperoxia in cell culture media that can affect a wide variety of cellular activities and may compromise the ability of in vitro models to reproduce in vivo biology. Here, we review and discuss some specific O2 -consuming organelles and enzymes, including mitochondria, NADPH oxidases, the transplasma membrane redox system, nitric oxide synthases, xanthine oxidase, and monoamine oxidase with respect to their sensitivities to O2 levels. Many of these produce reactive oxygen and/or nitrogen species (ROS/RNS) as either primary end products or byproducts and are acutely sensitive to O2 levels in the range from 1% to 18%. Interestingly, many of them are also transcriptional targets of hypoxia-inducible factors (HIFs) and chronic cell growth at physioxia versus 18% O2 may alter their expression. Aquaporins, which facilitate hydrogen peroxide diffusion into and out of cells, are also regulated by HIFs, indicating that O2 levels may affect intercellular communication via hydrogen peroxide. The O2 sensitivities of these important activities emphasize the importance of maintaining physioxia in culture.